(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Understanding the causal relationships among energy consumption, carbon dioxide (CO2) emissions, and economic growth is essential for informing sustainable development policies and addressing environmental challenges. This article conducts an econometric analysis to investigate the complex interplay between these variables. Drawing on a comprehensive dataset and employing advanced econometric techniques, the study explores the direction and strength of causal relationships, considering both short-term dynamics and long-term trends. The findings contribute to a deeper understanding of the intricate interactions between energy consumption, CO2 emissions, and economic growth, providing valuable insights for policymakers, researchers, and stakeholders in fostering environmentally sustainable economic development.